Breakthrough daptomycin-, linezolid-, vancomycin-resistant Enterococcus faecium bacteremia during protracted daptomycin therapy: A case report - Nathan B. Pincus; Tejas Joshi; Samuel W.M. Gatesy; Omar Al-Heeti; W. Justin Moore; Kelly E.R. Bachta (IDCases, 2022)
Infections with multidrug resistant (MDR) Enterococcus faecium (Efm) are a growing problem. Vancomycin resistance in enterococci has long challenged treatment, necessitating the use of linezolid or daptomycin. Subsequently, daptomycin-, linezolid-, vancomycin-resistant Efm (DLVRE) infections have emerged. Case reports and guidelines for treating DLVRE infections are limited. Here, we describe the clinical and laboratory management of an MDR Efm protracted intraabdominal (IA) infection and breakthrough DLVRE bacteremia. Serial Efm resistance was evaluated using whole genome sequencing (WGS), susceptibility testing, and synergy analysis. Prior to in vitro synergy testing, combination antimicrobial therapy with daptomycin (DAP) and ceftaroline (CPT) was employed to treat the patient’s central line-associated DLVRE bloodstream infection. In vitro antimicrobial testing revealed no synergy between daptomycin and ceftaroline; however, the patient’s bacteremia cleared following initiation of both in conjunction with catheter removal. Sequencing of the DLVRE isolates revealed multiple genomic mutations which explained both linezolid and daptomycin resistance phenotypes and confirmed the presence of a plasmid containing the vanA operon. Sequential WGS of two additional bacterial isolates from the same patient revealed protracted colonization with a single DLVRE clone and suggested the development of bacterial subpopulations. Pairing clinical isolate susceptibilities with WGS and synergy testing should be encouraged in clinical practice to better inform antimicrobial management in cases of multidrug resistance.